A strategy for building shared understanding in requirements engineering activities - Agredo Delgado, Vanessa (2022)
The requirements allow the development team to clearly understand the needs that the customer intends to be solved by the system, in this sense, understanding the context, capturing, negotiating, specifying, verifying, validating, and prioritizing the requirements may seem a relatively simple task, but there is a need to have a correct communication, and throughout this process, many changes and reprocesses occur due to misinterpretation or lack of information, in addition to considering that in the teams that perform these activities participate people from different disciplines, business units, cultures, with different levels of experience and therefore, each one will have different ways of perceiving the tasks, the key problems, which give meaning to the requirements according to their situation and knowledge, without having a joint base of homogeneous understanding within the team. Therefore, this work proposes a strategy for the construction of a shared understanding in the activities of requirements engineering, where its completeness, usefulness, and ease of use were validated, through an experiment executed as part of the development process of a software tool for the management of information and data processing of an agricultural and livestock association in Cauca. Using the conceptual, methodological, and validation cycle of the multi-cycle action research methodology, it was concluded that the strategy is complete and useful, but it is not easy to use, because its definition contains several elements that are difficult to handle, and it lacks adequate support to support and facilitate its application.